Trends in Substance Use Disorder-related Admissions at a Safety-net Hospital, 2008 – 2020. Issue 3 (May 2022) - Lindsay, Amber R.; Shearer, Riley D.; Bart, Gavin; Winkelman, Tyler N.A.
Abstract : Objectives: Safety-net hospitals disproportionately care for people with substance use disorders (SUDs), yet little is known about trends in hospital admissions related to specific substances. This study uses electronic health record data to describe trends in substance-specific admissions at a Midwest urban safety-net hospital. Methods: We included all admissions from 2008 through 2020 and defined them as non-SUD (N = 154, 477) or SUD-related (N = 63, 667). We described patient characteristics and trends in substance-specific admissions. We estimated the association of SUD diagnoses with discharge against medical advice and length of stay using logistic regression and generalized linear models. Results: Between 2008 and 2020, SUD-related admissions increased from 23.1% to 32.9% of total admissions. Admissions related to SUD had significantly more comorbidities than non-SUD-related admissions (4.7 vs 3.5, P < 0.001). Among illicit substances, cocaine-related admissions were the most common in 2008 (3.9% of total admissions, 17.2% of SUD admissions) whereas psychostimulants (eg, methamphetamines) were the most common in 2020 (7.8% of total admissions, 23.8% of SUD admissions). SUD-related hospitalizations had higher rates of against medical advice discharge (3.8%; 95% CI 3.6–3.9 vs 1.4%; 95% CI 1.3–1.4) and longer length of stay (6.3 days; 95% CI: 6.2–6.3 vs 5.3 days; 95% CI: 5.3–5.4) than non-SUD-related admissions. Conclusions: Over the study period, the proportion of admissions related to substance use rose to approximately one third of all admissions, driven by a rapidly increasing share of psychostimulant-related admissions. Identifying substance use patterns quickly using electronic health record data can help safety-net hospitals meet the needs of their patients and improve outcomes.